PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis sp.) YANG DIPELIHARA MENGGUNAKAN MEDIA GALON - Afriansyah, Azmi; Revita Syefti Palmi; Ardhana Reswari Utami; Muhammad Nursan; Ade Dwi Sasanti; The Best Akbar Esa Putra (Clarias : Jurnal Perikanan Air Tawar, 2025)
Nile Tilapia (Oreochromis sp.) is one of the freshwater fishery commodities that has high economic value and wide adaptability to various environmental conditions. This fish is known to be able to survive in varying temperatures and water qualities, and it has a fast growth rate. Therefore, it is widely cultivated on both an industrial and household scale. This study evaluated the growth and survival of tilapia (Oreochromis sp) in a gallon-based aquaculture system for 30 days at the Experimental Pond, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University. Two groups with uniform feed and density were observed for growth in length, weight, survival rate (SR), and water quality. Results were showed a survival rate of gallons A 33.3%, absolute length 2.4 cm and absolute weight 3.27 g. Meanwhile, the survival rate of gallons B 91.6%, with absolute length of 2.73 cm, and absolute weight 2.54 g. Water quality throughout cultivation was in an optimum range for temperature (27-31°C) and pH (6-9). This kind of system is considered effective for small-scale tilapia farming in limited areas with proper management.